CREATION OF CENTRALIZED STATE FOUNDATIONS BY AMIR TEMUR - Begimqulova Laylo Mashrabovna (TARIXIY TADQIQOTLAR, 2026)
This article describes how Amir Temur, after ascending the throne of Transoxiana in May 1370, ended the feudal fragmentation that prevailed in the country, founded a single centralized great state, and governed the country through Kurultai on the basis of the principles of consultation, justice, and representation in state administration. The historical contribution of Sahibkiran to statehood and the role of the administrative system he created in the development of medieval Eastern statehood are revealed.